The Development of the Palatal Fricative [γ′] in Old English - Cырохватова В. П. (Kalbotyra, 1981)
The voiced palatalized consonant [γ′] has remained in the dorsal subsystem till the end of the OE period. The chronology of this phonological change is proved by the graphic data of the interchange of the voiced and voiceless fricatives γ/x in intervocal and in final positions and by the thorough analysis of the symbols representing OE [γ′] and [j] (the latter possessing a considerable articulatory similarity with the sound [γ′]).